Collaborative Learning Action Cell (CLAC) mentoring program to self-efficacy of the out-of-field senior high school teachers - Cristie S. Sumbilla; Lurry Clare S. Trogo; Merlita C. Luntao (Universitas Airlangga, 2022)
Teachers teaching not their field of specialization is unavoidable; thus, structural support must be in place so that the school supports these teachers. Considering this prevalence, the study aimed to determine the effects of the collaborative learning action cell (CLAC) mentoring program on the self-efficacy of the out-of-field Senior High School (SHS) teachers of New Lucena National Comprehensive High School during the second semester of the academic year 2018-2019. This action research utilized an experimental method specifically, the one-group pretest-posttest design. The participants of this study were the purposively selected 12 out-of-field SHS teachers. The research instrument adopted was the Ohio State teacher efficacy scale (OSTES) to capture a broad range of capabilities necessary for good teaching. The results of the study revealed that the level of self-efficacy of the out-of-field SHS teachers is